Patients, healthcare providers, and general population preferences for hemodialysis vascular access: a discrete choice experiment - Wong, Tak-Sui; Chen, Qian; Liu, Taoran; Yu, Jing; Gao, Yangyang; He, Yan; Zhong, Qiongqiong; Tan, Zijian; Liu, Tinlun; Lu, Jian; Huang, Jian; Zhang, Casper J. P.; et al. (Frontiers in Public Health, 2024)
Background: A patient-centered dialysis treatment option requires an understanding of patient preferences for alternative vascular accesses and nephrologists often face difficulties when recommending vascular access to end-stage kidney disease (ESKD) patients. We aimed to quantify the relative importance of various vascular access characteristics to patients, healthcare providers and general population, and how they affect acceptability for patients and healthcare providers.In a discrete choice experiment, patients with maintenance hemodialysis (MHD), healthcare providers, and individuals from the general population were invited to respond to a series of hypothetical vascular access scenarios that differed in five attributes: cumulative patency, infection rate, thrombosis rate, cost, and time to maturation. We estimated the respondents' preference heterogeneity and relative importance of the attributes with a mixed logit model (MXL) and predicted the willingness to pay (WTP) of respondents via a multinomial logit model (MNL).Results: Healthcare providers (n = 316) and the general population (n=268) exhibited a favorable inclination towards longer cumulative patency, lower access infection rate and lower access thrombosis rate. In contrast, the patients (n=253) showed a preference for a 3-year cumulative patency, 8% access infection rate, 35% access thrombosis rate and 1.5 access maturity time, with only the 3-year cumulative patency reaching statistical significance. Among the three respondent groups, the general population found cumulative patency less important than healthcare providers and patients did. Patients demonstrated the highest WTP for cumulative patency, indicating a willingness to pay an extra RMB24,720(US3,708) for each additional year of patency time.Patients and healthcare providers had a strong preference for vascular access with superior patency. While the general population preferred vascular access with lower thrombosis rates. These results indicate that most patients prefer autogenous arteriovenous fistula (AVF) as an appropriate choice for vascular access due to its superior patency and lower complications than other vascular access types.